Biomechanics analysis of kicking motion - Mohd Haziq, Nordin (2013)
High quality kicking technique is the most important aspect of the football player. The good technique will increase quality of the game. This study will focus on the biomechanics analysis on the ten male Majlis Sukan Negeri Terengganu (MSNT) football players as well as to clarify the difference between three types of step run using kinematic variables and electromyography analysis. Electromyography data management and analysis are using Origin Pro 8.5.1 software and the statistical analysis carried out by using the ANOVA analysis. In order to observe the kicking motion experiment, the subjects will perform the instep kicking on the plane of activity in the laboratory. The image of the instep kicking was shot using high speed camera (250Hz). The subject tried to kick a ball at their full strength for each kick, namely the one step kick, two step kick and three step kick. The results indicate that there was no great difference in performance between the muscle of Quadriceps and Hamstring to the pairing of the three types of step run, though muscle discharge of the Calves and Tibialis Anterior show greater values in the group of pairing the three type of step. Image of the instep kicking was captured during the study and is useful to get the data of the kicking action for the kinematic variables. In this context, kinematics variable can be determine such as leg velocity, ball velocity, ball deformation, coefficient of restitution (COR) and force by leg. Based on the investigation with same leg velocity after impact which is 16 m/s, the highest force for leg is 5378.95N and the highest ball velocity is 23.07 m/s. The maximum ball deformation and coefficient of restitution noted as 0.018m and 0.86. These finding led to the conclusion that in a comparison between the kicking, three steps run demonstrates higher kinematics variables value compared to the one step and two step of kick.